2014
DOI: 10.1186/s12879-014-0642-9
|View full text |Cite
|
Sign up to set email alerts
|

Recreational drug use and risks of HIV and sexually transmitted infections among Chinese men who have sex with men: Mediation through multiple sexual partnerships

Abstract: BackgroundRecreational drug use (RDU) may result in sexual disinhibition and higher risk for HIV and other sexually transmitted infections (STIs) among men who have sex with men (MSM) in China. We assessed whether RDU was associated with HIV, syphilis, and herpes simplex virus type 2 (HSV-2) within the context of multiple sexual partnerships and unprotected sex.MethodsWe conducted a cross-sectional study among sexually-active MSM in six Chinese cities (Kunming, Jinan, Changsha, Zhengzhou, Nanjing, and Shanghai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
41
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 56 publications
(48 citation statements)
references
References 34 publications
7
41
0
Order By: Relevance
“…These HIV infection risk factors were also reported by previous studies in MSM [17, 20, 27, 28]. Our findings indicate that public health officials should pay attention to relevant contextual factors that may promote HIV infection, including UAI with homosexual partners and concurrent STD infection.…”
Section: Discussionsupporting
confidence: 87%
“…These HIV infection risk factors were also reported by previous studies in MSM [17, 20, 27, 28]. Our findings indicate that public health officials should pay attention to relevant contextual factors that may promote HIV infection, including UAI with homosexual partners and concurrent STD infection.…”
Section: Discussionsupporting
confidence: 87%
“…These differences may be due to the increasing use of poppers among Chinese MSM in recent years, as global data indicated that popper has become more and more population among MSM in recent years [11,14,2123]. However, the usage rate of popper among Chinese MSM is much lower than the findings of two UK studies (53.3% in Brighton, [21], and 64.9% in London 64.9%[24]), which may be due to the fact that are legal in sex shops, clubs and bars in these cities.…”
Section: Discussionmentioning
confidence: 99%
“…China presents a unique opportunity to examine these correlations. In China, recreational drug use has increased considerably among MSM in recent years [13], and an alarmingly high rate of recreational drug use has been observed among Chinese MSM[14]. In addition, gay app use has been relatively widespread [15] and rapidly adopted [16] among Chinese MSM.…”
Section: Introductionmentioning
confidence: 99%
“…17 It is worth mentioning that when this policy was established, MSM did not largely represent in the HIV epidemic, and therefore did not receive adequate attention from the government commensurate with its focus on other key populations (e.g., former plasma donors, PWID, FSW). [17][18][19][20][21] Hence, MSMfriendly programs were late in development, often without a clear risk reduction strategy and HIV-related service provision policy. Thus, HIV-positive MSM had low utilization of HIV-related services despite their high risk.…”
Section: Introductionmentioning
confidence: 99%